Acute effects of prolonged intermittent low-intensity isometric warm-up schemes on jump, sprint, and agility performance in collegiate soccer players - Haris Pojskic; Jeffrey C Pagaduan; Fuad Babajic; Edin Uzicanin; Melika Muratovic; Mario Tomljanovic (Biology of Sport, 2015)
The aim of the present study was to compare the effects of different warm-up interventions on jump, sprint and agility performance in collegiate soccer players. Twenty-one healthy male college soccer players (age: 20.14 ± 1.65 years; body height: 179.9 ± 8.34 cm; body mass: 74.4 ± 13.0 kg; % body fat: 9.45 ± 4.8) participated in the study. Subjects underwent four different randomized warm-up protocols separated by at least 48 hours. The warm-up schemes were: 1. no conditioning contraction protocol (NCC); 2. dynamic stretching (DS); 3. prolonged intermittent low-intensity isometric exercise (ST); and, 4. ST with an additional external load equal to 30% of body weight (ST + 30% BW). All interventions were preceded by a general warm-up. Results from one-way repeated measures ANOVA demonstrated a significant difference in countermovement jump (CMJ) at F(3,60) = 10.2, ηρ 2 = 0.337, p < 0.01. Post hoc analysis revealed a significant difference in CMJ performance in DS when compared to NCC and ST + 30% BW. No significant difference in CMJ was observed between DS and ST. CMJ scores in NCC, ST, and ST + 30% BW were non-significant. There was a significant difference in speed; F(3, 60) = 6.61, ηρ 2 = 0.248, p < 0.01. Post hoc analysis revealed significantly better time in DS than NCC and ST. However, no difference in speed was observed between DS and ST + 30% BW. Similarly, speed was similar in NCC, ST and ST + 30% BW. A significant difference in agility performance was also observed; F(3, 60) = 24.1, ηρ 2 = 0.546, p < 0.01. Post hoc analysis revealed significantly greater performance gains in DS than NCC. No significant difference in agility was observed in DS, ST and ST + 30% BW. In conclusion, a prolonged intermittent low-intensity isometric protocol using bodyweight only showed similar benefits with dynamic stretching in countermovement jump performance. When the same isometric condition with additional load equal to 30% of bodyweight was applied, effects in speed and agility were similar to dynamic stretching.